SiCN Nanofibers with a Diameter Below 100 nm Synthesized via Concerted Block Copolymer Formation, Microphase Separation, and Crosslinking. Issue 7 (19th November 2012) - Pillai, Saravana K. T.; Kretschmer, Winfried P.; Denner, Christine; Motz, Günter; Hund, Markus; Fery, Andreas; Trebbin, Martin; Förster, Stefan; Kempe, Rhett
<x xml:space="preserve">Abstract</x> Ultrathin SiCN fibers are produced from inexpensive carbosilazane‐polyethylene block copolymers. The two‐step synthesis consists of a concerted block copolymer formation, microphase separation and crosslinking step, followed by pyrolysis. The fibers have a mean diameter of 45 nm and an aspect ratio of up to 100. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>